TECHNOLOGY OF GROWING SWEET PEPPER IN GREENHOUSES - Mamayusupov Abbos Nurkobilovich; Loloyev Otabek Fakhriddin (Galaxy International Interdisciplinary Research Journal, 2022)
All spice (Latin appiit Capsicum) is an annual plant native to Central America (Mexico, Guatemala). A valuable vegetable crop is also known in Uzbekistan as Bulgarian pepper (Bulgarian). After the discovery of the American continent, sweet pepper quickly spread throughout Europe and Asia. Pepper first began to be cultivated in Spain and Portugal in the 15th century, and then spread to Italy, Algeria, Asia and the Mediterranean countries in the middle of the 16th century. From this period, the pepper was known to other Asian and African countries by the Portuguese. Sweet pepper was brought to Russia in the 16th century through Turkey and Iran. It is important that sweet pepper was first grown on the territory of Uzbekistan by Bulgarian peasants in the vicinity of Tashkent.